2013
DOI: 10.1590/s1809-98232013000200018
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de uma linha de cuidados para o idoso: hierarquização da atenção baseada na capacidade funcional

Abstract: ResumoO propósito deste artigo de atualização é contribuir para a estruturação de uma linha completa de cuidados para os idosos. Trata-se de um modelo baseado na identificação precoce dos riscos de fragilização dos usuários. Uma vez identificado o risco, a prioridade é a reabilitação precoce, a fim de reduzir o impacto das condições crônicas na funcionalidade. Partindo do pressuposto de que é adequado hierarquizar o processo de cuidado segundo as perdas funcionais que ocorrem com o passar dos anos, são estabel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
38

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 2 publications
0
13
0
38
Order By: Relevance
“…As found in literature 1,2,10 , the older elderly persons included in the survey had several chronic diseases. Literature also describes a high frequency of auditory and visual deficit among the elderly 11,12 , a fact that while not quantified in the present study, was observed, though not described.…”
Section: Discussionmentioning
confidence: 77%
“…As found in literature 1,2,10 , the older elderly persons included in the survey had several chronic diseases. Literature also describes a high frequency of auditory and visual deficit among the elderly 11,12 , a fact that while not quantified in the present study, was observed, though not described.…”
Section: Discussionmentioning
confidence: 77%
“…The idea is to monitor health, not disease, with the intention of postponing illness so that the elderly can enjoy their remaining time. Thus, the best strategy for the proper care of the elderly is based on the permanent monitoring of their health and keeping them under continuous observation, varying only the levels, intensity and context of the intervention 8 .…”
Section: Introductionmentioning
confidence: 99%
“…They should direct good practice, be based on the best evidence available and be appropriate for each clinical situation. The therapeutic plan guides the flow of the care pathway, and establishes the care route according to the needs of the patient 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Ribeiro et al (2008) Em relação às múltiplas doenças, os dados são semelhantes aos de estudos populacionais realizados no país. Observa-se a maioria dos idosos apresenta duas ou mais doenças, sendo mais prevalente a hipertensão arterial e as doenças articulares Barreto;Giatti, 2003;Louvison, 2006;Nunes et al, 2010; (Guerra et al, 2001;Won, Díaz, 2007;Carret et al, 2011 Ainda observa-se que o modelo de atenção está voltado para ações curativistas e não para ações de promoção da saúde (Veras et al, 2013 Os possíveis motivos para a maior utilização dos serviços de alta complexidade (urgência/emergência e internação) esta relacionado a multimorbidade e polifarmácia. Pela dificuldade no acesso ao serviço de saúde, o que gera o não acompanhamento de sua saúde levando a uma descompensação da doença e recorre primeiramente aos serviços de urgência/emergência e pela gravidade da doença, precisam ser hospitalizados.…”
Section: Discussionunclassified
“…Nota-se que o modelo atual é inadequado e anacrônico com uma péssima relação custo-benefício (Veras et al, 2013).…”
Section: Segundo Determinação Do Programa "Melhor Em Casa" Dounclassified